Basal Cell Carcinoma of the Head and Neck Region: A Retrospective Analysis of Completely Excised 331 Cases - Duriye Deniz Demirseren; Candemir Ceran; Berrak Aksam; Mustafa Erol Demirseren; Ahmet Metin (Journal of Skin Cancer)
The aim of the study is to analyze all completely excised BCCs in the head and neck region with regard to age, sex, personal and familial history, skin type, tumor localization and size, histopathological subtype of tumor, reconstruction method, and recurrence rates. Incompletely excised BCCs were not included in this study since incomplete excision is the most important preventable risk factor for recurrence. In 320 patients, 331 lesions were retrospectively evaluated by dividing into the following 8 subunits: scalp, frontotemporal, orbital, nose, cheek, auricula, perioral, and chin-neck area. Most of the patients were in 60–70 age group (34.7%). The nose (32.3%) was the most common site of presentation. Clinically, all lesions and, histopathologically, most of the lesions (42.2%) presented were of the nodular type. All cases of recurrence after complete excision (n=9, 2.7%) were located in the median parts of the head and neck region and were mainly diagnosed histopathologically as sclerotic and micronodular. Even though completely excised, head and neck region BCCs, especially which are more prone to recurrence due to anatomical and histopathological properties, should be more closely monitored in order to decrease morbidity and health care costs.